ARTISTIC DA'WAH: THE ROLE OF CONTEMPORARY FEMALE NASYID AS PERFORMING ARTS IN SPREADING ISLAMIC VALUES IN INDONESIA - Idwar, Agus; Adnan, Mohammad; Sirojuddin, Sirojuddin; Farhanullah, Farhanullah; Ramadhan, Thoriq Akmal (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
This study explores the intersection of performing arts and Islamic preaching (da'wah) by examining the role of contemporary female nasyid artists in Indonesia. Nasyid, traditionally a male-dominated genre of Islamic vocal music, has evolved into a platform where female artists such as Nissa Sabyan, Ai Khodijah, and Alma Esbeye creatively convey Islamic messages through music. This research aims to investigate how these artists integrate artistic expressions with Islamic values, how their performances resonate with audiences, and the extent to which their art contributes to the propagation of moderate Islam in the modern era. Employing a qualitative approach, data is gathered through content analysis of song lyrics, visual analysis of music videos, and interviews with key stakeholders, including artists and fans. The findings reveal that female nasyid artists utilize aesthetics, symbolism, and digital platforms to deliver religious messages, appealing to a broad demographic, especially younger audiences. This study contributes to the scholarly discourse on performing arts and literary expressions, shedding light on how contemporary Islamic preaching adapts to cultural and artistic dynamics, aligning with the journal's focus on literary theories and artistic exploration.